Associations of genetically predicted circulating levels of cytokines with telomere length: a Mendelian randomization study - Pan, Renbing; Xiao, Mingjia; Wu, Zhigang; Liu, Jingwen; Wan, Lijun (Frontiers in Immunology, 2023)
Background Telomere length (TL) has been regarded as a biomarker of aging, and TL shortening is associated with numerous chronic illnesses. The mounting evidence has shown that inflammatory cytokines are involved in maintaining or shortening TL, the causality of cytokines with TL remains unknown. Therefore, we performed a two-sample Mendelian randomization (MR) analysis to estimate the underlying correlations of circulating inflammatory cytokines with TL. Methods Genetic instrumental variables for inflammatory cytokines were identified through a genome-wide association study (GWAS) involving 8,293 European individuals. Summary statistics of TL were derived from a UK Bio-bank cohort comprising 472,174 samples of individuals with European descent. We employed the inverse-variance weighted (IVW) approach as our main analysis, and to ensure the reliability of our findings, we also conducted additional analyses including the weighted median, MR-Egger, MR pleiotropy residual sum and outlier test, and weighted model. Lastly, the reverse MR analyses were performed to estimate the likelihood of inverse causality between TL and the cytokines identified in the forward MR analysis. Cochran’s Q test were employed to quantify the degree of heterogeneity. Results After applying Bonferroni correction, a higher circulating level of Interleukin-7 (IL-7) was suggestively associated with TL maintaining (OR:1.01, 95%CI:1.00-1.02, P=0.032 by IVW method). The study also revealed suggestive evidence indicating the involvement of Interleukin-2 receptor, alpha subunit (IL-2Rα) level was negatively associated with TL maintaining (OR:0.98, 95%CI:0.96-1.00, P=0.045 by IVW method), and the weighted median approach was consistent (OR:0.99, 95%CI:0.97-1.00, P=0.035). According to the findings of reverse MR analysis, no significant causal relationship between TL and cytokines was explored. Our analysis did not reveal any substantial heterogeneity in the Single nucleotide polymorphisms or horizontal pleiotropy. Conclusions Our MR analysis yielded suggestive evidence supporting the causality between circulating IL-7 and IL-2Rα and telomere length, necessitating further investigations to elucidate the mechanisms by which these inflammatory cytokines may impact the progression of telomeres.